مباني دار عبد اللطيف - بن قويدر, سامية (جامعة الوادي - University of Eloued, 2022)
يهدف هذا البحث إلى إبراز أهمية الدراسات الكرونولوجية للمباني الأثرية لوضعها في إطارها التاريخي الصحيح الذي تنتمي إليه بعيدا عن التشويه والتحوير، من خلال التعمق في المصادر وتشخيص المواد الأولية وتقنيات البناء لمعرفة تنميطها وفق مجالها الزمني. لتحقيق ذلك اخترنا عينة دراسة متمثلة في درا عبد اللطيف التي بنيت على مراحل مختلفة لنبين أهمية هذا النوع من الأبحاث، خصوصا وأن المباني المضافة إلى هذه الدار مقلدة عن المباني العثمانية الأصلية، وأن تقليدها هذا كذلك يعطيها خصوصية كبيرة كذلك تجعلها من أبرز الشواهد المادية على بدايات الطراز النيوموريسكي بالجزائر. This research aims to highlight the importance of chronological studies of the archeological buildings in order to place them in their right historical frame to which they belong, far from any deformation and modification, and this is done by going deeply in the resources and diagnosing the raw materials and techniques of construction in order to be acquainted with their profiling according to their time frame. And for that purpose we have selected a study sample consisting of Dar Abdellatif which was built in different periods in order to highlight the importance of this type of research, knowing in particular that the constructions added to this building are imitated from the original ottoman buildings, and this imitation gives to it a significant particularity making it one of the main material witnesses of the Neo-Moorish style in Algeria.
دراسة كرونولوجية
مقال
Keywords: دار عبد اللطيف؛ المباني العثمانية؛ الطراز النيوموريسكي ؛ كرونولوجيا; Dar Abdellatif; Ottoman building ; Neo-Moorish style; Chronology